Hongos micorrizicos arbusculares en la rizósfera de genotipos promisorios de Cacao (Theobroma Cacao l.) bajo los sistemas tradicional y bajo bosque en la región San Martín. - Rojas García, José Carlos (2010)
The current research is developed at the experimental farm “El Choclino” ubicated in the district of Banda de shilcayo. This work was done in order to contribute to the widespread knowledge about Arbuscular Mycorrhizal fungi which is found in rhizosphere of promising genotype of cacao and which is also produced by two different systems of production in the district of San Martin, where its colonization area was identified, its population was quantified and Arbuscular Mycorrhizal fungi and its gender was determined. Many samples were collected in two periods of the year and a Randomized Complete Block Design (RCBD) with three replicates was used which was adjusted to factorial arrangement 2 X11. Different factors and levels of studies were the followings: systems of production (Low forest system and traditional system) ; genotypes of cacao (ICT – 2142, CCN – 51, ICT – 1112 , ICT – 1026, ICT – 2162, ICT-2171, ICS-95, UF-613, U-30, H-35, Hybrid). The results indicate that during humid time, the highest percentage of colonization of the evaluated genotypes was found in the low forest system, about 82.04%, whereas a lower percentage of colonization was identified in the traditional system, about 65.25%. On the other side, during dry time, the traditional system showed more percentage of colonization 65.76% compared to that percentage which was generated in the low forest 56.46%. In the number of spores that are located in the low forest system during the humid time, a big population of HMA with 7164.24 spores/ 100gr on land, was found, while, the traditional system presented a less population of HMA with 564649 spores /100gr on land. Nevertheless during the dry period, a big numbers of spores with 683.04/100gr on land can be observed on the low forest system and a less number with 370.59 spores /100gr on land was also observed in the traditional system. 21 morphotypes related to gender, glomus and acaulospora were identified, although glomus gender was the most prevailing on lands where belonged to those systems of production.